PENERAPAN ALGORITMA CRAWLING DALAM OTOMATISASI PEMBAYARAN ADMINISTRASI SEKOLAH - Sudiryanto, Gun; Tamrin, Teguh; Kusumodestoni, R. Hadapiningradja; Leksono, Bagus Bowo (Jurnal Disprotek, 2024)
APPLICATION OF CRAWLING ALGORITHM IN AUTOMATION OF SCHOOL ADMINISTRATION PAYMENTSNetwork system administration is the job of network administrators who are tasked with managing a computer network, both on a small and large scale. MTs. Asysyafi'iyah is a madrasah that is not yet familiar with the system of developing applications that make the work of madrasa institutions easier. The large number of students results in the need for some administration that must be managed by Administrative Staff to further minimize and make time efficient in terms of managing madrasa administration. The problem discussed in this research is how the methods commonly used in payment systems are more effective, making it easier to obtain payment information and pay via Virtual Account by using an Android application. The aim of this research is to make it easier for parents/guardians in terms of administrative payments and to produce an application that can provide information for students, parents/guardians, administration staff and madrasa heads. The methods used in the data collection process are observation, interviews, Literature Study and Documentation. Processing Data that has been collected by researchers through literature studies will be used by researchers as direct field observations. Then, the results of interviews and documentation obtained directly from observations will be translated into programming language using the Rapid Application Development (RAD) method. Based on the results of the research and discussion, the conclusion of this research is: The Madrasah Administration payment application can make things easier for parents, guardians or students. , simplify the work of Madrasah Administrative Staff in structuring payment administration better and can reduce the error rate and obtain report results quickly and accurately, simplify the process of processing payment data and searching for Administrative report data, as well as data relating to Administrative payments stored computerized on Admin database.Administrasi sistem jaringan merupakan sebuah pekerjaan dari para administrator jaringan yang bertugas untuk mengatur sebuah jaringan komputer baik dalam skala kecil maupun skala besar. MTs. Asysyafiâ€™iyahÂ  merupakan madrasah yang belum mengenal sistemasi pengembangan penggunaan aplikasi yang memudahkan pekerjaan lembaga madrasah, banyaknya siswa mengakibatkan butuhnya beberapa administrasi yang harus di kelola Staf Tata Usaha untuk lebih meminimalisir dan mengefisien waktu dalam hal pengelolaan administrasi madrasah. Masalah yang dibahas dalam penelitian ini adalah bagaimana metode yang biasa digunakan pada sistem pembayaran dengan cara yang lebih efektif, mempermudah mendapatkan informasi pembayaran dan membayar secara Virtual Account dengan pemanfaatan aplikasi android. Tujuan penelitian ini berguna untuk mempermudah Orang Tua/Wali dalam hal pembayaran Administrasi dan Menghasilkan sebuah aplikasi yang dapat memberikan informasi bagi Siswa Siswi, Orang Tua/Wali, Staf Tata Usaha dan Kepala Madrasah.Metode yang dilakukan dalam proses pengumpulan data adalah Observasi, Wawancara, Studi Pustaka, dan Dokumentasi. Pengolahan Data yang telah dikumpulkan oleh peneliti melalui studi pustaka akan digunakan peneliti sebagai observasi lapangan secara langsung. Kemudian dimana hasil wawancara dan dokumentasi yang diperoleh secara langsung dari observasi akan diterjemahkan kedalam bahasa pemrograman dengan menggunakan metode Rapid Application Development (RAD).Berdasarkan hasil penelitian dan pembahasan maka kesimpulan dari penelitian ini adalah: Aplikasi pembayaran Administrasi Madrasah dapat mempermudah orang tua wali atau siswa, mempermudah pekerjaan Staf Tata Usaha Madrasah dalam penataan administrasi pembayaran yang lebih baik dan dapat mengurangi tingkat kesalahan serta diperoleh hasil laporan secara cepat dan tepat, memudahkan proses pengolahan data pembayaran serta pencarian data laporan Administrasi, serta data yang berhubungan dengan pembayaran Administrasi tersimpan secara terkomputerisasi pada database Admin.